The web repair behaviour of an orb spider. (May 2015) - Tew, Eleanor R.; Adamson, Alex; Hesselberg, Thomas
Abstract : The study of construction behaviour and animal architecture has yielded significant insights into many areas of animal behaviour including decision making, optimal foraging and behavioural plasticity. In addition, the fitness consequences of constructing nests, protective structures and traps have been amply demonstrated. However, surprisingly little effort has gone into the study of what happens when these structures become damaged. Here we used the orb spider Araneus diadematus to explore repair behaviour of its web, with the aim of understanding environmental and structural influences on the repair process. The primary function of a spider web is to catch prey, so its structural integrity is of critical importance. However, orb webs are fragile structures and often become damaged, leading to the need to either repair or rebuild the web. Environmental conditions such as wind increase the likelihood of damage to the web. Here we first described and analysed the full repair process and quantified how effectively the repair restores structural integrity. Second, we investigated how wind affects repair behaviour and the spiders' anticipation of damage or motivation to repair. We found that spiders followed the same sequence of behaviours to repair damage to their webs and the repair significantly increased the effective web area following damage. Spiders reacted more quickly to damage in windy conditions, suggesting that they are attuned to the greater likelihood of damage in wind. Total repair time was the same in windy and control conditions, but repair was less effective in windy conditions. Highlights: We explore the web repair behaviour of the orb spider Araneus diadematus. We analyse the repair behaviour of orb spiders in detail for the first time. Spiders react to loss of tension in radial threads rather than web damage per se. Spiders react more quickly to damage in wind possibly due to enhanced attention. Differences in web repair behaviour suggest plasticity in repair decisions.